Synthesis of novel diflunisal hydrazide hydrazones as anti-hepatitis C virus agents and hepatocellular carcinoma inhibitors - ŞENKARDEŞ, SEVİL; KÜÇÜKGÜZEL, ŞÜKRİYE GÜNİZ (ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER, 2016)
Hepatitis C virus (HCV) infection is a main cause of chronic liver disease, leading to liver cirrhosis and hepatocellular carcinoma (HCC). The objective of our research was to develop effective agents against viral replication. We have previously identified the hydrazide hydrazone scaffold as a promising hepatitis C virus (HCV) and hepatocelluler inhibitor. Herein we describe the design a number of 2',4'-difluoro-4-hydroxy-N'-(arylmethylidene) biphenyl-3-carbohydrazide (3a-t) as anti-HCV and anticancer agents. Results from evaluation of anti-HCV activity indicated that most of the synthesized hydrazone derivatives inhibited viral replication in the Huh7/Rep-Feo1b and Huh 7.5-FGR-JCI-Rluc2A reporter systems. Antiproliferative activities of increasing concentrations of 2',4'-difluoro-4-hydroxy-N'-(2-pyridyl methylidene)biphenyl-3-carbohydrazide 3b and diflunisal (2.5-40 mu M) were assessed in liver cancer cell lines (Huh7, HepG2, Hep3B, Mahlavu, FOCUS and SNU-475) with sulforhodamine B assay for 72 h. Compound 3b with 2-pyridinyl group in the hydrazone part exhibited promising cytotoxic activity against all cell lines with IC50 values of 10, 1034 16.21 4.74, 9.29 and 8.33 mu M for Huh7, HepG2, Hep3B, Mahlavu, FOCUS and SNU-475 cells, respectively, and produced dramatic cell cycle arrest at SubG1/G0 phase as an indicator of apoptotic cell death induction. (C) 2015 Elsevier Masson SAS. All rights reserved.
Keywords: Diflunisal; Hydrazide-hydrazone; Hepatitis C; Hepatocellular carcinom; Antiviral; DEPENDENT RNA-POLYMERASE; NS5B POLYMERASE; BIOLOGICAL-ACTIVITIES; HCV NS5B; ANTICANCER; DERIVATIVES